A Decision Support System To Determine The Location Of A New Sales Branch At Star East Shop With The Smart Method - Nawawi, Ahmad; Ramadhani, Suci; Sihombing, Anton (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
In a business world that is always dynamic and full of competition, business people must always think of ways to continue to survive and if possible develop their business scale in order to meet these business needs, there are many ways that can be taken, one of which is by conducting data analysis. . Bintang Timur shop is one of the businesses in the field of iron and building material shops in the city of stabat. Bintang Timur shop was founded in 2013 which continues to grow at this time. Equipped with the desire to meet the needs of users in the field of iron and building, Bintang Timur store continues to grow by adding various products. The profits obtained in this shop are also used to develop the business, one of which is the addition of goods sold. Based on the analysis that has been done, there are several obstacles faced by this eastern star shop. One of them is the process of finding a new sales branch location at the Bintang Timur store. In this study, a Decision Support System (DSS) will be built using the Simple Multiple Attribute Rating Technique (SMART) method which is a multi-criteria decision making technique based on each alternative consisting of of a number of criteria that have a value and each criterion. Based on the calculation results of the SMART method above, Tebasan (A1) is a new branch location at the Bintang Timur Store in Stabat City which is feasible with a value of 0.763.